The Influence of Digital Transformation and Leverage on the Financial Performance of Companies in the Infrastructure, Transportation and Logistics Sector Listed on the IDX - Syamsil Huda; Yolandafitri Zulvia (International Journal of Economics and Management Research, 2024)
This study aims to analyze the effect of digital transformation and leverage on the financial performance of companies in the infrastructure, transportation and logistics sectors listed on the Indonesia Stock Exchange from 2019 to 2023. The population in this study were infrastructure, transportation and logistics companies listed on the Indonesia Stock Exchange. While the sample in this study was determined by the purposive sampling method, namely infrastructure, transportation and logistics companies for five consecutive years from 2019-2023 so that a sample size of 41 companies was obtained with 205 observation data. The analysis method used is the multiple linear regression method using the IBM SPSS Statistic 24 program. The results of this study conclude that digital transformation has a negative and significant effect on the company's financial performance, and leverage has a negative and significant effect on the company's financial performance.